Anti-cancer Therapy Leads to Increased Cardiovascular Susceptibility to COVID-19 - Lozahic, Caroline; Maddock, Helen; Sandhu, Hardip (Frontiers in Cardiovascular Medicine, 2021)
Please find abstract in the manuscript submitted. The abstract is exceeding the word limit, but has previously been approved by FCVM Editors.